1996
DOI: 10.1007/bf00210790
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of a novel matrix metalloproteinase inhibitor batimastat (BB-94) in patients with advanced cancer

Abstract: Degradation of basement membrane and extracellular matrix by matrix metalloproteinases (MMPs) is believed to be required for tumor invasion, tumor-induced angiogenesis and vascular invasion. A synthetic hydroxamate, batimastat (also known as BB-94), inhibits MMPs by binding the zinc ion in the active site of the MMP. Batimastat inhibits at least 50% of MMP activity at concentrations less than or equal to 10 ng/ml in vitro. Batimastat retarded ascites accumulation and increased survival in mice with human ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 11 publications
0
46
0
2
Order By: Relevance
“…This clearly suggests that expression of matrix metalloproteinase -9 is an early event in melanoma progression (Kerkela & Saarialho-Kere, 2003). Several studies using either cell lines or animal models have demonstrated that the balance between matrix metalloproteinases and their inhibitors finally determines melanoma progression (Hofmann et al, 2000b;Wojtowicz-Praga et al, 1998;Rudek et al, 2001;Jin et al, 2006;Wojtowicz-Praga et al, 1996;Bodey et al, 2001;Airola et al, 1999). Overexpression of TIMP-1, -2, and -3 significantly reduces melanoma tumour cell invasion, migration, growth and metastasis, and significantly reduces tumour neovascularization in several tumour models (Anand-Apte et al, 1996).…”
Section: Integrin Signalling and Extracellular Matrix Enzymesmentioning
confidence: 98%
“…This clearly suggests that expression of matrix metalloproteinase -9 is an early event in melanoma progression (Kerkela & Saarialho-Kere, 2003). Several studies using either cell lines or animal models have demonstrated that the balance between matrix metalloproteinases and their inhibitors finally determines melanoma progression (Hofmann et al, 2000b;Wojtowicz-Praga et al, 1998;Rudek et al, 2001;Jin et al, 2006;Wojtowicz-Praga et al, 1996;Bodey et al, 2001;Airola et al, 1999). Overexpression of TIMP-1, -2, and -3 significantly reduces melanoma tumour cell invasion, migration, growth and metastasis, and significantly reduces tumour neovascularization in several tumour models (Anand-Apte et al, 1996).…”
Section: Integrin Signalling and Extracellular Matrix Enzymesmentioning
confidence: 98%
“…These are pseudopeptide derivatives that mimic the cleavage site of MMP substrates (Wojtowicz-praga et al,1996). They act as competitive inhibitors which inhibit the MMP activity by interacting with the Zn 2+ in catalytic sites and then chelating it (Gialeli et al, 2011).…”
Section: Peptidomimetic Mmpimentioning
confidence: 99%
“…Batimastat is the first MMPI which was tested in humans, (Wojtowicz-praga et al, 1996) but it has broad spectrum of inhibition and low water solubility because of which its intraperitoneal administration is required. To overcome these drawbacks Marimastat was introduced which can be orally administered but associated with the side effects of musculoskeletal pain (Steward and Thomas, 2000).…”
Section: Peptidomimetic Mmpimentioning
confidence: 99%
“…Batimastat showed a poor oral bioavailability and also could not be given intravenously due to its limited solubility. Therefore clinical studies were performed using intraperitoneal or intrapleural administration [35][36][37][38]. Following intraperitoneal administration, rapid systemic absorption was seen with serum levels exceeding concentrations causing 50% inhibition (IC 50 ) of major MMPs for prolonged periods of time.…”
Section: Phase I Studiesmentioning
confidence: 99%